MENGUJI SENSITIVITAS RASIONALISASI PADA KEPUTUSAN MELAKUKAN KORUPSI DI INSTANSI PELAYANAN PUBLIK - Johann Tarru (Politeknik STIA LAN Makassar, 2018)
Refer to forensic accounting, the best way to combat corruption that is recognized the background behind the corrupt behavior. The public sector in Indonesia were surprised by the corruption perceptions index issued by Transparency International in early 2018, showed a deceleration corruption eradication efforts. Government institutions as the major in charge of the public sector get the spotlight from the public related to it. Therefore, the spirit of eradicate corruption need to be raised. Initially by trying to dissect the fraud triangle theory in order to find a suitable corruption prevention strategy for public sector agencies. This research intends to test the sensitivity of the 3 main variables: pressure, rationalization, and opportunity in the corruption prevention efforts. The sample used i.e. 47 people medical personnel at the Regional General Hospital Polewali Mandar Regency in West Sulawesi province. The incoming data is compiled and then analyzed using path analysis. The results of the analysis show that rationalization is the most effective variables in corruption prevention efforts in public agencies.